Machine learning for finance the practical guide to using data-driven algorithms in banking, insurance, and investments - Klaas, Jannes (Expert insight, 2019)
Machine Learning for Finance shows you how to build machine learning models for use in financial services organizations. It shows you how to work with all the key machine learning models, from simple regression to advanced neural networks. You will use machine learning to automate manual tasks, address systematic bias, and find new insights ...